Genomic analyses identify 15 risk loci and reveal HDAC2 , SOX2-OT , and IGF2BP2 in a naturally occurring canine model of gastric cancer - Shawna R. Cook; Sanne Hugen; Jessica J. Hayward; Thomas R. Famula; Janelle M. Belanger; Elizabeth McNiel; Hille Fieten; Anita M. Oberbauer; Peter A. J. Leegwater; Elaine A. Ostrander; Paul J. J. Mandigers; Jacquelyn M. Evans (Proceedings of the National Academy of Sciences, 2025)
Gastric cancer ranks as the fifth most common human cancer worldwide and has a poor survival rate and limited treatment options. Despite the high prevalence and mortality rate, the genetic etiology is largely unknown. In dogs, a clinically and histologically similar disease disproportionately affects two breeds, the Belgian Tervuren and Belgian Sheepdog, which develop the intestinal and diffuse tumor subtypes observed in humans. We performed a Bayesian genome-wide association study and selection analyses in this naturally occurring canine model to elucidate underlying genetic risk factors for gastric cancer and identified 15 associated loci. Variant filtering revealed germline putative regulatory variants for the EPAS1 ( HIF2A ) and PTEN genes and a coding variant in CD101 . Two loci are overrepresented among cases of intestinal tumor subtype. Although closely related to Tervuren and Sheepdogs, Belgian Malinois rarely develop gastric cancer. Across-breed analyses uncovered haplotypes enriched in Malinois at SOX2-OT and IGF2BP2 that are at significantly higher frequency among genome-wide association study controls. Among Tervuren and Sheepdogs, HDAC2 putative regulatory variants were present at comparatively high frequency and were associated with risk of gastric cancer. Here, we describe a complex genetic architecture governing gastric cancer in a dog model, including genes such as PDZRN3 and KLHL29 , that have not been associated with human gastric cancer.